Suitability of shoot apical meristem as explant to minimize variation of tobacco (nicotiana tabacum L. cv. Virginia) plantlets - Che Aziz, Azimah (2015)
A protocol for in vitro regeneration using shoot apical meristem (SAM) of tobacco (Nicotiana tabacum L. cv. Virginia) has been established and entire tobacco plantlets were produced. The explants were isolated from 5-days-old germinating tobacco seedlings. Shoot development and root formation were shown in all treatments but the most effective treatment is control with 73% of explant survival, followed by 0.5 mg/l IAA with 60% of explant survival. However, before acclimatization, plantlets from medium supplemented with 0.5 mg/l KIN showed the highest number of leaves and plantlet height with an average of 6.0 ± 0.37 leaves and 0.7 ± 0.04 cm height, followed by 1.0 mg/l KIN with an average of 5.4 ± 0.37 leaves and 0.6 ± 0.04 cm height. Number of roots was found highest in medium supplemented with 0.5 mg/l IAA with an average of 4.9 ± 0.18 roots followed by control medium with an average of 3.5 ± 0.23 roots. After 12 weeks of acclimatization, only plantlets from treatment with 0.5 mg/l IAA survived in the environmental condition. To detect the variation, the morphology, anatomy and primary metabolites between tobacco plants and its plantlets were compared. Both morphology (plant height, number of leaves and leaf morphology) and anatomy (midrib of leaf, stem and root) of tobacco plantlets were similar to tobacco plants. Besides, there is also no significant difference in the total chlorophyll, carbohydrate and protein content of both tobacco plants and plantlets. The secondary metabolites and anti-oxidative profiling between tobacco plants and its plantlets were also studied. Total flavonoid and carotenoid content were found higher than phenolic compounds in both plants. However, the antioxidant activity varied between both plants. Plantlets of tobacco have slightly higher antioxidant activity than tobacco plants. This was indicated by the significant difference (p<0.05) in the IC50 values between both plants in which plantlets have a lower IC50 value (16.82 ± 0.21) than tobacco plants (18.97 ± 0.28). In conclusion, no variation was expressed in tobacco plantlets regenerated from SAM in vitro except for a slightly different in the IC50 values. Tobacco plants and its plantlets can also be considered as good sources of natural antioxidant.